2017
DOI: 10.1080/00324728.2017.1319495
|View full text |Cite
|
Sign up to set email alerts
|

Differences in labour force participation by motherhood status among second-generation Turkish and majority women across Europe

Abstract: Second-generation Turkish immigrants make up an increasingly important segment of European labour markets. These young adults are entering the prime working ages and forming families. However, we have only a limited understanding of the relationship between labour force participation and parenthood among second-generation Turkish women. Using unique data from the Integration of the European Second Generation survey (2007/08), we compared the labour force participation of second-generation Turkish women with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 61 publications
2
32
0
Order By: Relevance
“…The limited existing research on family formation and female labour force participation in migrant populations has mainly adopted a cross-sectional approach and reports contradictory results. Holland and de Valk (2017) find that employment of second-generation women of Turkish origin in Germany, the Netherlands, France and Sweden is lower compared to natives. Differences between Turkish origin mothers and non-mothers are similar to differences between native mothers and non-mothers, suggesting that the transition to motherhood has the same effect on employment for both groups.…”
Section: The Link Between Family Formation and Labour Market Attachmementioning
confidence: 75%
See 2 more Smart Citations
“…The limited existing research on family formation and female labour force participation in migrant populations has mainly adopted a cross-sectional approach and reports contradictory results. Holland and de Valk (2017) find that employment of second-generation women of Turkish origin in Germany, the Netherlands, France and Sweden is lower compared to natives. Differences between Turkish origin mothers and non-mothers are similar to differences between native mothers and non-mothers, suggesting that the transition to motherhood has the same effect on employment for both groups.…”
Section: The Link Between Family Formation and Labour Market Attachmementioning
confidence: 75%
“…Research specifically focussing on the labour force participation of migrant mothers is limited, however, and frequently based on cross-sectional data (Holland and de Valk 2017;Rubin et al 2008;Bevelander and Groeneveld 2012;Dale et al 2006;Bevelander and Groeneveld 2006). In cross-sectional studies, women having children are compared to women who have not yet had children as well as women who will never enter parenthood, making it complicated to distinguish the effect of family formation from selection effects and the effects of structural factors that already determine employment positions (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immigrants are often driven into the less promising labour markets, although there may be substantial differences across the groups. However, despite the fact that the second generation shows an increase in competitive capacity, as indicated by their higher level of education, and despite the diversification of their social networks, as well as their familiarity with the language and culture of the receiving society, the gap between this generation and the native population may have diminished, but still persists (Andriessen, Fernee, and Wittebrood 2014;Dagevos and Huijnk 2016;Holland and De Valk 2017;Van Ours and Veenman 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that having a child has a negative impact on labour force participation (Gustafsson et al 1996) and this is reported for both majority group women as well as those of migrant origin (Andersson and Scott 2005;Holland and de Valk 2014;Lundström and Andersson 2012). Women with minor children, are given the age of their children in need of childcare and at the same time also often have ageing parents.…”
Section: Introductionmentioning
confidence: 99%